'On the programme tonight': The Old Grey Whistle Test as tastemaker for British AOR audiences in the early 1970s. Issue 3 (7th October 2020) - Bennett, Andy
Abstract : British popular music television series The Old Grey Whistle Test (OGWT) was a regular feature on BBC2 between 1971 and 1987. The show enjoyed its greatest popularity during the early 1970s when, as a programme synonymous with the term album-orientated rock (AOR), it was responsible for introducing British popular music audiences to a different range of music than was generally featured on national television and radio at the time. Despite its iconic and relatively unique status during the early 1970s, however, little has been written about OGWT. The purpose of this article is to examine and assess the significance of OGWT in terms of its critical role as a tastemaker for British AOR audiences during an era where opportunities to listen to AOR on British television and radio were limited. The article also considers the legacy of OGWT in the digital age where its significant archival footprint on YouTube has given the show a renewed level of importance as a comprehensive retrospective guide to the AOR music of the early 1970s.